Economic fluctuations in Central and Eastern Europe - the facts - Péter Benczúr; Attila Rátfai (Magyar Nemzeti Bank, 2005)
We carry out a detailed analysis of quarterly frequency dynamics in macroeconomic aggregates in twelve countries of Central and Eastern Europe. The facts we document include the variability and persistence in and the co-movement among output, and other major real and nominal variables. We find that consumption is highly volatile and government spending is procyclical. Gross fixed capital formation is highly volatile. Net exports are countercyclical. Imports are procyclical, much more than exports. Exports are most procyclical and persistent in open countries. Labor market variables are all highly volatile. Employment is lagging, and often procyclical. Real wages are dominantly procyclical. Productivity is dominantly procyclical and coincidental. Private credit is procyclical and dominantly lagging the cycle. The CPI is countercyclical, and is weakly leading or coincidental. The cyclicality of inflation is unclear, but its relative volatility is low. Net capital flows are mostly leading and procyclical and exhibit low persistence. Nominal interest rates are in general smooth and persistent. The nominal exchange rate is more persistent than the real one. Overall, we find that fluctuations in CEE countries are larger than in industrial countries, and are of similar size than in other emerging economies. This is particularly true about private consumption. The co-movement of variables, however, shows a large degree of similarity. A notable exception is government spending: unlike in industrial economies, it is rather procyclical in transition economies. The findings also indicate that Croatia and the accession group show broadly similar cyclical behavior to industrial countries. The most frequent country outliers are Bulgaria, Romania and Russia, especially in labor market, price and exchange rate variables. Excluding these countries from the sample makes many of the observed patterns in cyclical dynamics quite homogenous.
Keywords: E32; 330; Business Cycle Facts; Central and Eastern Europe; Konjunktur; Konjunkturindikator; Vergleich; Osteuropa